Practice of riddles in development of children’s cognitive skills - Gučienė, G. (Psichologija, 1968)
Educational value of riddles has been long known, whereas their impact on the cognitive skills of children has not been fully revealed yet. The methods of riddle asking and guessing, applied in kindergartens, do not always ensure children’s conscious involvement in such practices.Considering the fact that the main educational-upbringing meaning of the riddle games is directed at that mental activity in which a child is currently involved, we have made a series of experiments with the aim to establish how significant activities with riddles are to the development of cognitive skills in pre-school children group in kindergartens. Besides, we have set a goal to determine the conditions and means owing to which the educational impact of riddles reaches its highest efficiency. Two experiments have been performed. The first experiment served to investigate the very process of reading a riddle. For this purpose, 4 series of visual aids were prepared. The aim of the second experiment was the investigation of the impact of riddle reading on the development of cognitive skills in children, when a long-term work with riddles is involved in conversations with children, excursions and other practices.Experiments have shown that such work with riddles helps to: 1) revive the images of relevant things or phenomena possessed in the memories of children; 2) activate children’s thinking processes, especially in development of analytical, comparative, generalization and systemization skills. Alongside, it has been established that by asking a riddle in a pre-school group, an important role is played by visual aids prepared in such way as to activate a child’s imagination and thinking, without providing the direct answer. The analyzed children underwent all series of tasks; 3) besides, each series of visual aids helped to establish some traits of riddle reading by children.The first series was prepared according to the traditional method when the content of a picture provides the answer (Picture 1). The results of investigation with the material of this series allowed us to critically assess the albums of riddles widely used in kindergartens, because the pictures used in the 1st series of investigation were composed the same way as the albums of riddles. Such pictures including the direct answers do not boost children’s thinking much. They rely to a large extent on children’s memories and, therefore, do not significantly encourage their thinking processes.The second series includes riddles with metaphorical description of details of the guessed objects. Visual aids depict the parts of details of objects presented in the riddle texts according to which children had to synthesize the guessed object (Picture 2). The riddles of the 2nd series were helpful in upbringing children’s abilities to synthesize. By laying pictures, children would establish the order of elements in general scheme and discover functional links among such elements.The third series were complex riddles made up of several pictures. While working with these riddles, pictures were analyzed, with the aim to discover one guessed object disguised in all these pictures via generalization (e.g., riddle about earth, Picture 3). Guessing process of these riddles was difficult for children but, by using the pictures, in most cases they would cope with the task. Thus, visual aids in this series have conditioned training of generalization operations in children by means of riddles.The fourth series was riddles expressed in metaphors. This series includes a couple of pictures, with one of them depicting the riddle text, and the other-the answer. A child has to choose from several answer-pictures the correct one and put it next to the picture depicting the riddle text (Picture 4). In this case the pictures not only helped to guess the riddles, but also to understand the metaphor and this is complicated for the children of such age.A conclusion may be made that application of visual aids increases the role of riddles in intellectual development of children. Moreover, it was revealed that in using riddles during the practices in pre-school groups, it is purposeful to retain a certain distance between the observed object and the riddle about it, as contrary to what has been often done up till now. This ensures greater activeness of children’s minds. Reading riddles about the objects which are directly observed is only recommended for junior groups.
Keywords: riddles; cognitive development; development of cognitive skills